(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda upholds the prevention of disease by observing strict daily and seasonal regimen and regulating natural urges. The concept of natural urges is an inimitable notion of Ayurveda. Though feces and urine which are Mala (excretory end products), are included in these needs, sweat, the third one is excluded. The major reasons for these may be that Sweda has its root all over the body in the form of adipose tissue and sweat glands and there was no control or environmental restriction of perspiration elicited in ancient days. Moreover, Perspiration is controlled by the Autonomic nervous system which steers the involuntary actions of the body. In current days of sedentary lifestyle, severe climatic variations and use of external thermoregulatory methods like air-condition have changed the scenario. This can inhibit or alter perspiration resulting in several skin disorders and metabolic aberrations. These conditions demand a deliberation on reconsidering the importance of Sweda and its impact on health in a novel perspective. Though regulation voluntarily is not mandated in Ayurveda classics in its specific context, present day claim a stress free and active life style to “perspire properly”. This paper explores importance of Sweda (sweat/ perspiration) and possible reason for excluding it from natural urges.